GEOMORPHOLOGICAL FEATURES OF SIDAMULYA, SUKABUMI REGENCY, CILETUH PALABUHANRATU UGG - PUTRI, NISRINA NADELLIA; Pratiwi, Santi Dwi; Rosana, Mega Fatimah (Faculty of Geological Engineering, Universitas Padjadjaran, 2025)
The Sidamulya region, located in the Ciracap Subdistrict of Sukabumi Regency, forms part of the Ciletuh Palabuhanratu UNESCO Global Geopark (UGG) and exhibits unique geomorphological features influenced by geological structures and surface processes. This study focuses on analyzing the area’s geomorphology through morphographic, morphometric, and morphogenetic aspects using Digital Elevation Model (DEM) data processed via ArcGIS and field verification. The research identifies five geomorphological units, including denudational and volcanic hills with varying slope gradients, drainage patterns, and lithological compositions. These units are shaped by exogenic processes such as erosion, weathering, and sedimentation, with lithologies including sandstone, breccia, and andesitic-basaltic lava. The thematic maps produced from this study provide valuable insights into the region’s landscape evolution and contribute to sustainable management within the geopark area. Keyword: Sidamulya, Morphography, Morphometric, Morphogenetic, Geomorphology